The Influence of Leadership Style, Academic Culture, Motivation, Gender and School Status on Teacher Success in Learning Indonesian Language and Literature in SMP - Arisandi, Ulyma Tahara; Suryaman , Maman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of leadership style, academic culture, teacher motivation, gender and school status on teacher success in learning Indonesian Language and Literature at SMP in Bangka Regency. This type of research uses quantitative descriptive using an ex post facto approach. Population in study This are 81 junior high school Indonesian Language and Literature teachers in Bangka Regency , consisting of from 35 state, private and MTs schools taken use technique purposive sampling . Technique analysis of the data used that is analysis path (path analysis). The results of the research show that there is an influence of leadership style, academic culture, teacher motivation, gender and school status on teacher success in learning with a Sig value of 0.00 ≤ 0.050.